Improve Performance of Water-based Drilling Fluids - Abdul Razak Ismail (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
The significant of exploring deep wells is increasing rapidly to fulfill the global oil and gas demand. Deepwater drilling in offshore operations found negative impact on the drilling fluids rheological properties when exposed to high pressure high temperature conditions. Hence, designing drilling fluids for drilling in these type of wells are the major challenges. In this study, the impact of multi-walled carbon nanotube (MWCNT) and nano metal oxides (titanium oxide, aluminum oxide and copper oxide) on the rheological properties of water based drilling fluid were investigated. The influence of different concentrations of nanoparticles on the rheological properties of water-based drilling fluid was investigated at room and elevated temperatures. The experimental results showed that the filtrate loss of the water-based drilling fluid is reduced around 65% and mud cake thickness is reduced about 30% in the presence of 1 g of MWCNT. Water-based drilling fluid with metal oxide also produced low filtrate loss. For example, water-based drilling fluid plus titanium oxide achieved more than 50% reduction in fluid loss and the filter cake thickness reduced to about 30%. Furthermore, significant improvements are seen in the rheological properties such as yield point, plastic viscosity and gel strength of the water-based drilling fluid with the presence of metal oxide and MWCNT. Overall, the application of nanoparticles on the rheological properties of water-based drilling fluid delivers on great benefits.